Ppb-level NH3 Sensing Utilizing MoS2 Nanoflowers Towards Developing Exhaled-Breath based Point-of-Care Diagnosis of Chronic Kidney Diseases - Chakraborty, Bikramdeb; Bhattacharyya, Partha (2023 8th International Conference on Computers and Devices for Communication (CODEC), 2023)
This study explores the potential of detecting renal failure and chronic kidney diseases (CKD) by analyzing elevated ammonia (NH 3 ) levels in exhaled breath, offering a non-invasive, point-of-care diagnostic approach. Healthy individuals exhibit NH 3 levels between 50 and 1500 ppb in exhaled breath, whereas those with renal dysfunction display concentrations from 1500 to 15000 ppb. The research develops a cost-effective, rapid-response NH 3 sensor using MoS 2 nanoflowers, demonstrating impressive performance with a response magnitude (RM) of around 40% at 100 ppm NH 3 and a response time of 92 seconds. It also achieves a limit of detection (LoD) at 100 ppb NH 3 , with an RM of approximately 5% and a response time of 37 seconds. Even in humid conditions (95% relative humidity), the sensor maintains its limit of detection (LoD), making it a valuable tool for early diagnosis. This work addresses the pressing need for renal disease detection and showcases the potential of Transition Metal Dichalcogenide (TMDC) materials for cost-effective, non-invasive NH 3 sensing.